The role of barrier function of mucous membranes in allergic diseases and sublingual allergen-specific immunotherapy - Oksana M. Kurbacheva; Miramgul E. Amanturlieva (Бюллетень сибирской медицины)
Currently one of the factors of allergy predisposition is the increase in barrier permeability of the mucous membranes of the respiratory system and the gastrointestinal tract (GIT). It defines the probability of an emergence of an allergic response. To understand the mechanisms of the interaction of the mucous membranes of different systems that explain their common function is undoubtedly necessary for discussion of this problem. The features of microbiome influence and the changes of the microbiome state during the formation of the immune response to the contact with allergens are of particular interest. The structure of the epithelial barrier of the airwaysand GIT, and mechanisms of allergen transport through barrier systems with the subsequent interaction with the cells (?) associated with barrier fabrics have been considered. The possible role of the barrier function of mucous membranes in conducting sublingual allergen-specific immunotherapy (SLIT) is discussed.